Inteligencia de mercados para la exportación de rosas de la finca “Angelique Flowers” del cantón Espejo provincia del Carchi - Cevallos Montesdeoca, Telmo Bryan (2025)
Angelique Flowers begins in 2015, with 2.50 hectares of suitable and fertile land located in the canton Espejo province of Carchi, is located more than 3,100 meters high, important factor to obtain a flower with all the characteristics of the word “quality”, the marketing is done locally and nationally and is in international negotiations to enter the international market with the product. The objective of the research is to carry out a market intelligence for the export of natural roses from the farm “Angelique Flowers” to the German market, knowing that the company currently wants to internationalize its product. As a means of search we work with information from official web pages such as TradeMap, ProEcuador. In addition, research instruments are applied to collect data in order to take the necessary measures to carry out the export plan and the implementation of the project. Fresh roses cover the local demand and now with this research it is determined that the market to export is Germany, being the country that has the greatest acceptance\; it is also worth mentioning that the internationalization of several Ecuadorian companies and brands that expanded to international markets have shown that there are opportunities to grow in specific niches.